The Name-glorifying projects of Alexei Losev and Pavel Florensky: A question of their historical interrelation - Biriukov, Dmitry (Studies in East European thought, 2025)
This article deals with the question of the interrelation between two papers, both called, in short, “Onomatodoxy”, dedicated to the doctrine of Name-glorification ( Imiaslavie , Onomatodoxy), both of which were created in line with the Neo-Patristic movement in the Russian philosophy of the Silver Age. One of these papers is by Alexei Losev and the other by Pavel Florensky. In my opinion, there are sufficient grounds to state that Losev’s “Onomatodoxy” was written either after Florensky created his own “Onomatodoxy”, i.e., after November 1922, or, at the earliest, after Florensky started to give clandestine lectures about Onomatodoxy in Moscow (where Losev lived), i.e., not earlier than spring 1921. Therefore, Losev’s article “Onomatodoxy” could have been intended for the religious-philosophical collection of articles planned for publishing by Yaschenko in 1922 in Berlin.